COVID-19: Does SARS-CoV-2 Modulate Acanthamoeba Epigenetics to Enhance Survival and Transmission in the Environment? - Muhammad, Jibran Sualeh (ACS Pharmacol Transl Sci, 2021)
[Image: see text] For the first time, we propose the role of epigenetic mechanisms in severe acute respiratory syndrome coronavirus-2 survival inside Acanthamoeba and possible transmission via airborne cysts.